The Influence of Intensive Physical Training on Salivary Adipokine Levels in Elite Rhythmic Gymnasts - Roupas, N. D.; Mamali, I.; Armeni, A. K.; Markantes, G. K.; Theodoropoulou, A.; Alexandrides, T. K.; Leglise, M.; Markou, K. B.; Georgopoulos, N. A. (Hormone and Metabolic Research, 2012)
Exercise challenges homeostasis and establishes a new dynamic equilibrium. Elite Rhythmic Gymnasts (RG’s) begin exercise at an early age, undergo physical and psychological stress, and adopt negative energy balance to retain a lean physique. The aim of the present study was to evaluate the effect of negative energy balance, acute and chronic exercise on salivary adiponectin, resistin and visfatin levels and their interaction with salivary cortisol, and insulin levels in elite RG’s. This study is unique in character, as all variables were assessed on the field of competition. The study included 51 elite RG’s participating in “Kalamata 2010 World Cup” in Kalamata, Greece on April 2010. Twenty-seven healthy age-matched girls were used as controls. Anthropometric values were assessed; baseline and post exercise salivary cortisol, insulin, adiponectin, resistin, and visfatin levels were measured. Comparisons regarding hormonal features between RG’s and controls were adjusted for BMI and body fat percentage. Salivary adiponectin levels were higher (p<0.05) and visfatin lower (p=0.094) in RG’s compared with controls, while no significant changes were observed regarding salivary cortisol, insulin, and resistin levels. In elite RG’s acute intensive anaerobic exercise led to increased salivary insulin levels (p<0.001), reduced salivary adiponectin (p<0.001) and visfatin levels (p<0.05), and no changes in salivary resistin levels. Moreover, diurnal variation of salivary cortisol was lost. In elite RG’s salivary adiponectin is upregulated and salivary visfatin is downregulated after chronic intensive exercise and negative energy balance, while both salivary adiponectin and visfatin levels are suppressed after short term intensive anaerobic exercise.
Keywords: adipose tissue; resistin; visfatin; adiponectin; saliva; exercise